Lithium and cobalt co-doped mesoporous bioactive glass nanoparticles promote osteogenesis and angiogenesis in bone regeneration - Zhang, Xin; Nan, Kai; Zhang, Yuankai; Song, Keke; Geng, Zilong; Shang, Donglong; Fan, Lihong (Frontiers in Bioengineering and Biotechnology, 2024)
Healing of severe fractures and bone defects involves many complex biological processes, including angiogenesis and osteogenesis, presenting significant clinical challenges. Biomaterials used for bone tissue engineering often possess multiple functions to meet these challenges, including proangiogenic, proosteogenic, and antibacterial properties. We fabricated lithium and cobalt codoped mesoporous bioactive glass nanoparticles (Li-Co-MBGNs) using a modified sol-gel method. Physicochemical analysis revealed that the nanoparticles had high specific surface areas (> 600 m 2 /g) and a mesoporous structure suitable for hydroxyapatite (HA) formation and sustained release of therapeutic ions. In vitro experiments with Li-Co-MBGNs showed that these promoted angiogenic properties in HUVECs and pro-osteogenesis abilities in BMSCs by releasing Co 2+ and Li + ions. We observed their antibacterial activity against Staphylococcus aureus and Escherichia coli, indicating their potential applications in bone tissue engineering. Overall, our findings indicate the feasibility of its application in bone tissue engineering.